Interpretation of color in the Holy Qur’an and the hadith of the Prophet (Journal of the College of Basic Education, 2022)
Arab-Islamic art, the source of color richness, was and will remain a great treasure of countless images of colours. The murals, in their decoration inlaid with mosaics, appeared in spears, banners, brigades, poetry, clothing, and various arts such as drawing, calligraphy, decoration, pottery, miniatures, and decoration.Accordingly, the colors in the artistic creativity of the artists were seen and represented to them by characters they drew with their colors and lines, so they turned into vibrant color images, so it deserved to be devoted to a research of this level that revolves around its connotations and meanings for Arab Muslim artists.